The durability of cryogenic structure materials - Medved, Ivan; Tatarchenko, Halyna; Biloshytskyi, Mykola; Poddubny, Sergey (Academic journal Industrial Machine Building Civil Engineering, 2020)
According to world statistics, the main share of destruction in engineering practice occurs precisely because of fatigue, therefore, the fatigue problem is one of the most pressing scientific and technical problems of our time, which solution requires additional complex experimental and theoretical studies. The paper presents the experimental studies results of the effect of deep cooling on low-cycle fatigue and cyclic creep of stainless structural steel 03X20N16AG6 under conditions of a pulsating cycle of an external load change with a frequency of 0.033 s-1 (2 cycles/min) in air and environments of liquid refrigerants (nitrogen and helium) at temperatures of 293, 77 and 4.2 K, respectively
Keywords: structural alloys; deep cooling; low-cycle fatigue; cyclic creep